Rebooting India - Nilekani, Nandan and Shah, Viral (U.K Allen Lane, 2015)
"India is on its way to becoming a global powerhouse but in order to do so--and empower its expanding workforce--it needs to resolve the contradictions that distort society and bridge the gaps between its people. Nandan Nilekani and Viral Shah show how this can be done by using technology to radically reimagine government itself.
Include Index,Notes and Illustration
Keywords: India -- Economic development -- Public administration